Tell el-Dabca XXIV: The Late Middle Kingdom Settlement of Area A/II A Holistic Study of Non-élite Inhabitants at Tell el-Dabca, Vol. 1 - Bader, Bettina (2020)
This book comprises the final excavation report of the western part of the late Middle Kingdom settlement in Area A (ca 1830 to 1700 BC) excavated from 1966 to 1969. Included are a comprehensive description of the archaeology, the architecture and all relevant finds.Book: http://e-book.fwf.ac.at/o:1453Map: http://e-book.fwf.ac.at/o:1454